Tanzania Economic Update, July 2021 : Transforming Tourism - Toward a Sustainable, Resilient, and Inclusive Sector - World Bank (World Bank, Washington, DC, 2021)
The pandemic severely disrupted economic activity in Tanzania, and the World Bank’s latest firm-level data suggest that the situation had only modestly improved by the end of 2020. New data sources show that COVID-19 continues to weigh heavily on employment and income. Data for the first quarter of 2021 suggest that recovery remains fragile and uneven across sectors, but economic activity could accelerate in the second half of 2021. The tourism-dependent economy of Zanzibar has been particularly impacted by the COVID-19 crisis. Tanzania’s macroeconomic framework remains sound, with low inflation and moderate external and fiscal vulnerabilities.